1985
DOI: 10.1090/s0002-9947-1985-0787953-3
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous Borel sets of ambiguous class two

Abstract: Abstract.We describe and characterize all homogeneous subsets of the Cantor set which are both an F"s and a GSo; it turns out that there are wx such spaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…A Wadge-minimal example is the space T = X 1 2 from [8], [5]; its Wadge class isĎ 2 (Σ 0 2 ). A minimal first category example (not quite as trivially; see [6] or [7]) is Q×T = X 1 3 , of Wadge class D 3 (Σ 0 2 ). Second, does there exist a non-homogeneous space whose square is homogeneous but not a group?…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A Wadge-minimal example is the space T = X 1 2 from [8], [5]; its Wadge class isĎ 2 (Σ 0 2 ). A minimal first category example (not quite as trivially; see [6] or [7]) is Q×T = X 1 3 , of Wadge class D 3 (Σ 0 2 ). Second, does there exist a non-homogeneous space whose square is homogeneous but not a group?…”
Section: Discussionmentioning
confidence: 99%
“…In [7] it was shown that all homogeneous spaces in ∆ 0 3 contain a countable (or, in just a few cases, a σ-compact) dense subset such that any relative Π 0 2 -set in the space which contains it is actually homeomorphic to the space. In this section we will extend this result to arbitrary homogeneous Borel sets.…”
Section: The Main Lemmamentioning
confidence: 99%
See 1 more Smart Citation
“…Van Engelen (see [E4,Theorem 4.7]) proved that if the Cantor set C is densely homogeneous with respect to an h-homogeneous space A, then C is densely homogeneous with respect to the product Q×A. Theorem 3.4 generalize this result for the non-separable case.…”
mentioning
confidence: 89%
“…Together with [1], where all homogeneous Borel sets in 2" of class A°3 were determined, this yields a complete topological classification of all zero-dimensional homogeneous absolute Borel sets. Roughly, using the inductive definition of the non-self-dual Borel Wadge classes as given by Louveau [5], we show that the Wadge class of a non-A°3 homogeneous Borel set in 2" is non-self-dual and reasonably closed (for definitions, see below); then we can apply a theorem of Steel [8] to get what we want.…”
mentioning
confidence: 99%